Request for payment of outstanding amount and issue of work completion certificate for piling and D-wall - Brac University (Brac University, 2023)
This record consists of general correspondence regarding the request for payment of outstanding amount and issue of work completion certificate for piling and D-wall of BRAC University new campus project.